SISTEM PELARASAN PADA GAMELAN KYAI KANJENG - Agus Setiawan; Muhammad Nur Salim; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
This article is a research that aims to determine the tunning system in Gamelan Kyai Kanjeng and the factors that influence the tunning system in Gamelan Kyai Kanjeng. This research combines two methods, namely, qualitative and quantitative. Qualitative data collection techniques were carried out using literature studies, observations, interviews and documentation studies. The quantitative data collection technique in this research was carried out by recording tones and measuring the frequency of Kyai Kanjeng’s Gamelan. The results of the research show that the tunning system in Gamelan Kyai Kanjeng is a flexible tunning system that can cover several music genres with diatonic tonality. The tunning system applied to Kyai Kanjeng’s Gamelan is influenced by several factors including the influence of Emha Ainun Nadjib, the empirical experience of gamelan makers and the repertoire of Kyai Kanjeng.